2023
DOI: 10.1186/s12903-023-03298-z
|View full text |Cite
|
Sign up to set email alerts
|

The effect of nanobased irrigants on the root canal dentin microhardness: an ex-vivo study

Safoora Sahebi,
Hossein Mofidi,
Abbas Abbaszadegan
et al.

Abstract: Background Given the favorable antimicrobial properties of zinc oxide (ZnONPs), standard silver (AgNPs), and imidazolium-based silver (Im-AgNPs) nanoparticles, this study aimed to evaluate their influence on the microhardness of root canal dentin. Methods In this experimental study, 40 mandibular premolars were decoronated at the cementoenamel junction and longitudinally sectioned into halves to create 80 specimens. They were randomly allocated to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…Irrigation with AgNPs may influence the biochemical properties of root dentin. Syringe irrigation with a standard AgNP solution for 15 min decreased the microhardness of root canal dentin in the apical and coronal thirds [ 141 ]. Conversely, Jowkar et al demonstrated that using AgNP nanoparticles as the final irrigant improved the fracture resistance of teeth with previous endodontic treatment [ 142 ].…”
Section: The Application Of Nanomaterials Used In Endodonticsmentioning
confidence: 99%
“…Irrigation with AgNPs may influence the biochemical properties of root dentin. Syringe irrigation with a standard AgNP solution for 15 min decreased the microhardness of root canal dentin in the apical and coronal thirds [ 141 ]. Conversely, Jowkar et al demonstrated that using AgNP nanoparticles as the final irrigant improved the fracture resistance of teeth with previous endodontic treatment [ 142 ].…”
Section: The Application Of Nanomaterials Used In Endodonticsmentioning
confidence: 99%